A randomized controlled trial of a compassion-centered spiritual health intervention to improve hospital inpatient outcomes - Jennifer S. Mascaro; Patricia K. Palmer; Marcia J. Ash; Marianne P. Florian; Deanna M. Kaplan; Roman Palitsky; Steven P. Cole; Maureen Shelton; Charles L. Raison; George H. Grant (PLoS ONE, 2025)
Background Inpatient medical settings lack evidence-based spiritually integrated interventions to address patient care needs within a pluralistic religious landscape. To address this gap, CCSH™ (Compassion-Centered Spiritual Health) was developed to leverage the skillsets of healthcare chaplains to improve patient outcomes through spiritual consultation. Here, we report the results of a randomized, wait-list controlled, pre-registered (NCT03529812) study that evaluated the impact of CCSH on patient-reported depression and explored putative mediators of CCSH’s effects. Method Chaplain residents were randomized to be trained in CCSH as part of their clinical pastoral education (CPE) residency in the fall (n =  8) or spring semester (n =  8). After fall training, all residents provided spiritual consultations with hospitalized patients (n =  119; n =  54 seen by CCSH-trained chaplains). Those not yet trained to deliver CCSH provided a traditional consult. Patients’ pre-consult distress was measured using the National Comprehensive Cancer Network Distress Thermometer, and post-consult depression was measured using the Hospital Anxiety and Depression Scale (HADS). Consults were audio-recorded and transcribed verbatim, and we conducted linguistic analyses using LIWC 2015 software to quantify chaplain linguistic behavior. Results Patients seen by CCSH-trained chaplains had lower post-consult depression scores (M =  4.10, SD =  5.04) than patients who were seen by wait-listed chaplains (M =  6.12, SD =  5.08), after adjusting for pre-consult distress (p = .048). There was also a significant relationship between post-consult depression and chaplain LIWC clout scores (r =  -0.24, p = .017), a linguistic measure thought to reflect the expressive confidence and other-oriented focus of the speaker. An exploratory mediation model revealed an indirect effect of CCSH on patient depression through chaplain clout language b =  -0.11 (90% CI, -.257, -.003). Implications These data suggest that CCSH decreases patient depression among inpatients, in part due to CCSH-trained chaplains’ use of more inclusive, confident, and other-oriented language. We connect these findings with current understandings of effective clinical linguistic behavior and reflect on what this work may mean for integrated spiritual health care.